2012
DOI: 10.1038/onc.2012.193
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR is a negative prognostic factor and exhibits pro-oncogenic activity in pancreatic cancer

Abstract: HOTAIR is a long intervening non-coding RNA (lincRNA) that associates with the Polycomb Repressive Complex 2 (PRC2) and overexpression is correlated with poor survival for breast, colon and liver cancer patients. In this study, we show that HOTAIR expression is increased in pancreatic tumors compared to non-tumor tissue and is associated with more aggressive tumors. Knockdown of HOTAIR (siHOTAIR) by RNA interference shows that HOTAIR plays an important role in pancreatic cancer cell invasion and as reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
613
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(645 citation statements)
references
References 44 publications
22
613
0
10
Order By: Relevance
“…16,17 Accumulating studies have indicated that HOTAIR is upregulated in cancers including HCC. [18][19][20] It has been reported that HOTAIR regulates gene expression via epigenetic modifications. 21 For example, Rinn et al demonstrated that HOTAIR interacts with polycomb-repressive complex 2 (PRC2) to increase the trimethylation of histone H3 lysine-27 (H3K27), resulting in the reduction of HOXD gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Accumulating studies have indicated that HOTAIR is upregulated in cancers including HCC. [18][19][20] It has been reported that HOTAIR regulates gene expression via epigenetic modifications. 21 For example, Rinn et al demonstrated that HOTAIR interacts with polycomb-repressive complex 2 (PRC2) to increase the trimethylation of histone H3 lysine-27 (H3K27), resulting in the reduction of HOXD gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…11,16 In fact, previous studies have shown that particular deregulated lncRNAs are important regulators of tumor formation and progression. 17,24 For example, the antisense intergenic RNA HOX Antisense Intergenic RNA (HOTAIR) is highly expressed in multiple types of primary somatic tumors, such as hepatocellular carcinoma, 25,26 pancreatic cancer, 27 and gastric cancer, 28 as well as some metastatic tumors, including metastatic breast tumors 29 and melanoma. 30 Moreover, high HOTAIR level is associated with poor patient survival rate 20,27 and tumor recurrence.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…17,24 For example, the antisense intergenic RNA HOX Antisense Intergenic RNA (HOTAIR) is highly expressed in multiple types of primary somatic tumors, such as hepatocellular carcinoma, 25,26 pancreatic cancer, 27 and gastric cancer, 28 as well as some metastatic tumors, including metastatic breast tumors 29 and melanoma. 30 Moreover, high HOTAIR level is associated with poor patient survival rate 20,27 and tumor recurrence. 25 It was discovered that HOTAIR represses transcription across 40 kb of the HOXD locus by acting as a scaffold of histone modification complexes; it binds with polycomb chromatin remodeling complexes in trans, which lead to alterations of cells' epigenetic state and subsequent gene expression.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…Of note, a microarray analysis confirmed that lncRNAs HOX antisense intergenic RNA (HOAIR), CCAT1 and HIF1A‐AS1 were over‐expressed within retinoblastoma tissues, yet lncRNAs MIR31HG, BCAR4 and H193 were evidently under‐expressed within retinoblastoma tissues 13. Among them, HOTAIR was identified to be a cis‐acting parameter within the HOXC loca,14, 15, 16 and its carcinogenicity has been authenticated within breast cancer, liver cancer, colorectal cancer, oesophageal squamous cancer, pancreatic cancer, non‐small cell lung cancer and cervical cancer 17, 18, 19, 20, 21, 22, 23, 24. In addition, HOAIR was indicated as a potential therapeutic biomarker for retinoblastoma, and silencing of HOTAIR could attenuated proliferation, migration and invasion of retinoblastoma cells were determined after 25…”
Section: Introductionmentioning
confidence: 99%